Age-related decrease in expression of mitochondrial DNA encoded subunits of cytochrome c oxidase in Drosophila melanogaster - Sohal, Rajindar S. (2008)
A key feature of the aging process is that the mitochondrial respiratory capacity declines and production of reactive oxygen species increases in the later part of life span. In previous studies, cytochrome c oxidase (CcO), the terminal component of the mitochondrial electron transport chain, was found to be the only oxidoreductase exhibiting an age-related decrease in activity in Drosophila melanogaster. The present study tested the hypothesis that decreases in the abundance of catalytic subunits of CcO, encoded in mitochondrial DNA, could underlie the age-associated loss of enzyme activity. Protein amounts of subunits I, II and III, which form the catalytic core of CcO, were determined by immunoblot analysis in 15-, 25-, 35-, 47- and 60-day-old flies. Subunits II and III decreased with age by up to 43% and 75%, respectively, whereas the decrease in subunit I was only 15%. The results pinpoint specific changes in a component of the mitochondrial electron transport chain, which could underlie the age-related decrease in mitochondrial respiratory activity and an increase in oxidant production. Apparently, the stoichiometry of CcO holoprotein is dynamically altered during the aging process in Drosophila melanogaster.